Governance and human development in Sub-Saharan Africa - Fellingham, Stacey Joy (Graduate School of Business (GSB), 2024)
This study examines the interrelationship between governance, democracy, resource dependency, and human development in Africa. Specifically, the Human Development Index (HDI) and six governance indicators from the WGI database are employed to estimate a dynamic panel model on forty-eight sub-Sahara African countries throughout 1996 to 2019 using the Generalised Method of Moments (GMM) technique. The empirical analysis reveals a positive association between all six governance indicators and human development. ‘Voice and accountability', and ‘control of corruption', evidence a strong association with growth in human development followed by government effectiveness, rule of law, regulatory quality, and political stability. Interaction terms demonstrate that democratisation is essential to unlocking the benefits of the governance indicators on human development. The effects of the resource dependence on the interaction between governance and human development are less obvious than democratisation, likely due to the volatile nature of commodity prices which may only have short-term impacts. From the findings, this study recommends that human development will likely be fostered through support of the democratisation process. To drive democratisation, sub-Saharan states should consider diversifying their economies and adopting policies that reduce economic inequality